Evaluation of nutrient efficiency of carapace (crab shell) in agriculture sector - Alim, Samiul (International Journal of Agricultural Research, Innovation and Technology, 2023)
In the coastal region, crab cultivators are concerned about the wastage produced by crab moulting and polluting soil health for pisciculture. Farmers have recently been using different bio-compost, produced after decomposing as vegetable wastage, cow dung, Trico-compost and vermin-compost. The nutritional composition of carapace based on dry matter has been approximately analysed and indicates DM-97.33%, Moisture-2.67%, Crude protein, CP-0.02%, Ether extract, Lipid-2.12%, Crude fiber, CF-5.57% and Ash, Minerals-20.25%. After decomposing, the crab shell was used for BARI hybrid summer tomato production in a field trial to observe the plant vegetative and yield performance. In the field, trial has been set five (5) treatments with six (6) replications for each treatment as T1= control treatment, T2= Soil (50%) + vermin-compost (50%), T3= vermin-compost (100%), T4= Crab Shell compost (100%), T5=Soil (50%) + Crab Shell compost (25%) + Vermin-compost (25%). Crab shell compost has a significant relation to vermin compost for enhancing the leaf length of the plant. T4 was more significant than T2 and T5 for enhancing the leaf width of plants and average fruit weight. Crab shell compost is non-significance for increased tiller number, inflorescence number and plant height. T5 have a more significant relation than vermin-compost for increasing the tiller number of plant. After the field trial, the soil nutrient analysis report showed that alkalinity is on the optimum label for crop production. Decomposed crab shell-treated soil also increases Organic matter, Nitrogen, Potassium, Boron, Zinc, and salinity but reduces phosphorous compared to the control treatment. Therefore, the decomposed crab shell is a nutrient source for agricultural production. Int. J. Agril. Res. Innov. Tech. 13(1): 103-109, June 2023